Identification of the Nicotinamide Salvage Pathway as a New Toxification Route for Antimetabolites. Issue 4 (19th April 2018) - Buonvicino, Daniela; Mazzola, Francesca; Zamporlini, Federica; Resta, Francesco; Ranieri, Giuseppe; Camaioni, Emidio; Muzzi, Mirko; Zecchi, Riccardo; Pieraccini, Giuseppe; Dölle, Christian; Calamante, Massimo; Bartolucci, Gianluca; et al.
Summary: Interest in the modulation of nicotinamide adenine dinucleotide (NAD) metabolome is gaining great momentum because of its therapeutic potential in different human disorders. Suppression of nicotinamide salvage by nicotinamide phosphoribosyl transferase (NAMPT) inhibitors, however, gave inconclusive results in neoplastic patients because several metabolic routes circumvent the enzymatic block converging directly on nicotinamide mononucleotide adenylyl transferases (NMNATs) for NAD synthesis. Unfortunately, NMNAT inhibitors have not been identified. Here, we report the identification of Vacor as a substrate metabolized by the consecutive action of NAMPT and NMNAT2 into the NAD analog Vacor adenine dinucleotide (VAD). This leads to inhibition of both enzymes, as well as NAD-dependent dehydrogenases, thereby causing unprecedented rapid NAD depletion, glycolytic block, energy failure, and necrotic death of NMNAT2-proficient cancer cells. Conversely, lack of NMNAT2 expression confers complete resistance to Vacor. Remarkably, Vacor prompts VAD formation and growth suppression in NMNAT2-positive neuroblastoma and melanoma xenografts. Our data show the first evidence of harnessing the entire nicotinamide salvage pathway for antimetabolic strategies. Graphical Abstract: Highlights: NAMPT and NMNAT2 metabolize Vacor into the NAD analog VAD Vacor metabolism prompts NAD depletion and NAD-dependent dehydrogenase inhibition Vacor triggers necrosis of cancer cells and tumor xenografts expressing NMNAT2 The nicotinamide salvage pathway can be harnessed for antimetabolic strategies Abstract : Synthesis and consumption of the pyridine nucleotide NAD are increased in cancer cells and contribute to cell proliferation and neoplastic transformation. Buonvicino et al. identified Vacor as a new structure interfering with NAD metabolome which may lead to the development of new antineoplastic molecules.